Hubungan antara Ekspresi Heat Shock Protein-70 (HSP70) dengan Skor Risk of Ovarian Cancer Relapse (ROVAR) pada Pasien Kanker Ovarium Epitelial yang Dilakukan Operasi dan Dilanjutkan dengan Kemoterapi - Lilik Gretta Damaianty; Ardhanu Kusumanto; Agung Dewanto (JURNAL KESEHATAN REPRODUKSI, 2021)
Background: Ovarian cancer is one of the leading causes of death in gynecological malignancies which occupies the third place in the world.  One of largest challenge in epithelial ovarian cancer therapy is resistance to chemotherapy. Increased of  Heat Shock Protein-70 (HSP70) expression associated with the progressivity of tumor cells growth through the resistance process against chemotherapy, whereas Risk Of Ovarian Cancer Relapse (ROVAR) score is a tool that used to predict the ovarian cancer recurrence risk in patient who underwent surgery followed by chemotherapy.Objective: This study is aimed to evaluate the correlation between HSP70 expression and ROVAR score in patient with epithelial ovarian cancer who underwent first line therapy.   Method: This is a retrospective cohort study that involve 42 subjects with epithelial ovarian cancer who had been through surgery (optimal or suboptimal surgery) followed by chemotherapy.  Immunohistochemical staining of pre chemotherapy paraffin blocks was performed using HSP70 antibody and recurrence risk was calculated using ROVAR scores after surgery followed by chemotherapy. The external variables evaluated were age, parity, Body Mass Index (BMI), menopause history, and surgical type.  Data analysis used Chi Square test, spearman test, and logistic regression analysis.Result and Discussion: Of the total 42 subjects who met the inclusion criteria, most found in advanced stage with the age mean is 54,3 years old.  In the ROVAR score measurement, in high risk category is found about 32(76.19%), while in the medium risk and low risk category is 10 (23.81%). On the other hand, strong HSP70 expression was found in 36(85,71%), moderate HSP70 expression in 6(14,39%), and weak HSP70 expression was not found.  Based on Spearman's correlative test, there was a positive, very strong, and significant correlation between the expression of HSP70 and risk allocation according to ROVAR score (r=0.717, p=0.000). As well as in multivariate analysis, HSP70 expression had a statistically and clinically significant relationship with ROVAR score (p=0.017; RR 2.710; 95% CI 0.366-5.054) which strong HSP70 expression was 2.71 times more likely to have a high risk of recurrence according to ROVAR score.Conclusion: There is a positive, very strong, and significantly meaning between HSP70 expression and ROVAR score.  Increased in HSP70 expression may lead to increased recurrence risk according to ROVAR score.  Both could be used to predict recurrence in epithelial ovarian cancer post first line therapy.Keywords: Epithelial ovarian cancer, HSP70, ROVAR score, recurrence.